2018
DOI: 10.1002/ente.201700609
|View full text |Cite
|
Sign up to set email alerts
|

A Water‐Driven Triboelectric Generator for Electrocatalytic Wastewater Treatment

Abstract: Triboelectric generators (TEGs) have been shown to be advantageous at energy harvesting for sensors and portable devices. Here, a water‐driven triboelectric generator (WD‐TEG) powered wastewater treatment reactor that harvests energy from the water flow via the triboelectric effect is introduced. The WD‐TEG is an efficient and green approach towards wastewater treatment. With the electricity generated from WD‐TEG, a degradation efficiency of up to 80 % for estrogenic pollutants, estriol, and 17‐β estradiol is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…The n values of all the PP/CPH composites are close to the value n = 0.5, which indicated that the composites approached toward the Fickian diffusion behavior. Many literatures also reported that the water absorption behavior of natural filler that filled the thermoplastic composites was following the Fickian behavior . According to Table , the k and D values of the PP/CPH composites increased with the increasing of filler content.…”
Section: Resultsmentioning
confidence: 90%
“…The n values of all the PP/CPH composites are close to the value n = 0.5, which indicated that the composites approached toward the Fickian diffusion behavior. Many literatures also reported that the water absorption behavior of natural filler that filled the thermoplastic composites was following the Fickian behavior . According to Table , the k and D values of the PP/CPH composites increased with the increasing of filler content.…”
Section: Resultsmentioning
confidence: 90%
“…Therefore, a higher MLF content could lead to a higher amount of water absorption. Apart from the diffusion of water by the fibers, poor fiber‐matrix adhesion and fiber debonding from the matrix at higher fiber content could also contribute to the capillary mechanism, which involves the flow of water molecules into the interface region .…”
Section: Resultsmentioning
confidence: 99%
“…Alkali treatment is an effective and low‐cost surface modification of natural fibers. The alkali treatment creates changes in the surface energy and surface topography .…”
Section: Resultsmentioning
confidence: 99%